2021
DOI: 10.3390/ijms22031387
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Classification, and Expression Analysis of the Triacylglycerol Lipase (TGL) Gene Family Related to Abiotic Stresses in Tomato

Abstract: Triacylglycerol Lipases (TGLs) are the major enzymes involved in triacylglycerol catabolism. TGLs hydrolyze long-chain fatty acid triglycerides, which are involved in plant development and abiotic stress responses. Whereas most studies of TGLs have focused on seed oil metabolism and biofuel in plants, limited information is available regarding the genome-wide identification and characterization of the TGL gene family in tomato (Solanum lycopersicum L.). Based on the latest published tomato genome annotation IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In the plant body, lipases are responsible for the breakdown of triglycerides to glycerol and fatty acids [ 122 ]. Therefore, it can be concluded that Rhodiola crenulata provides more source of energy to resist high altitude adversity stress by breaking down glycerides and accumulating free fatty acids at higher altitudes, thus improving the resistibility against high altitude integrated adversity.…”
Section: Resultsmentioning
confidence: 99%
“…In the plant body, lipases are responsible for the breakdown of triglycerides to glycerol and fatty acids [ 122 ]. Therefore, it can be concluded that Rhodiola crenulata provides more source of energy to resist high altitude adversity stress by breaking down glycerides and accumulating free fatty acids at higher altitudes, thus improving the resistibility against high altitude integrated adversity.…”
Section: Resultsmentioning
confidence: 99%
“…These duplications occurred in genes situated on different chromosomes, indicating the segmental type of duplication being the main force of diversification [ 96 ]. Although segmental duplication preserves the primary functional group, it leads to differentiation in the manner of duplicated genes [ 142 ].…”
Section: Discussionmentioning
confidence: 99%
“…These duplications occurred in genes situated on different chromosomes, indicating the segmental type of duplication being the main force of diversification [93]. Although segmental duplication preserves the primary functional group, it leads to differentiation in the manner of duplicated genes [139].…”
Section: Discussionmentioning
confidence: 99%